2018
DOI: 10.5649/jjphcs.44.568
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Characteristics of Qualitative Evaluation System of Hand Hygiene

Abstract: Compliance with hand hygiene is important in infection control, and the rate of hand disinfectant application is rising in recent years. Therefore, we evaluated the qualitative evaluation system of hand hygiene by mechanically measuring hand disinfectants containing a fluorescence substance. We observed that the hospital staff and general population had a significantly higher application rate of hand disinfectant on the palm side than on the dorsal side (P < 0.05). Hospital staff had a significantly higher app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…If this is the case, then there is a risk that effective infection control measures are not in place. However, although numerous studies have been published on changes in rates of sterilisation and the effects of conducting surveys and training for medical professionals on hand disinfection [4][5][6][7][8][9][10][11][12], few have targeted citizens. A survey on hand hygiene among pharmacists (who are also considered medical professionals) found that the rate of correct answers regarding situations in which hand hygiene and procedures for the use of fast-drying hand disinfectants are required increased after training sessions were held [11].…”
Section: Introductionmentioning
confidence: 99%
“…If this is the case, then there is a risk that effective infection control measures are not in place. However, although numerous studies have been published on changes in rates of sterilisation and the effects of conducting surveys and training for medical professionals on hand disinfection [4][5][6][7][8][9][10][11][12], few have targeted citizens. A survey on hand hygiene among pharmacists (who are also considered medical professionals) found that the rate of correct answers regarding situations in which hand hygiene and procedures for the use of fast-drying hand disinfectants are required increased after training sessions were held [11].…”
Section: Introductionmentioning
confidence: 99%